Merleau-Ponty: between ontology and metaphysics - Ferraz, Marcus Sacrini A. (Cadernos Espinosanos, 2009)
In this article, we resume Michel Haar’s evaluation according to which Merleau-Ponty’s ontological project would redound to metaphysics. In order to make such an evaluation more rigorous, we propose another criterion, inspired by Kant, according to which Merleau-Ponty’s work could also be classified as metaphysical. After that, we elucidate Merleau-Ponty’s philosophical strategies on the basis of which we judge that neither according to Haar’s criterion nor according to the Kantian’s criterion constitutes Merleau-Ponty a metaphysical discourse.